Beijing’s ASEAN embrace : making hay while the sun shines - Ho, Benjamin (2014)
High profile visits by Xi Jinping to Indonesia and Malaysia in the past week have reinforced China's diplomatic outreach to ASEAN. With the United States paralysed by domestic wrangling, Bejing's embrace of ASEAN could potentially signify a pivotal shift in the balance of power in Asia, provided it acts judiciously.